2019
DOI: 10.1037/pspp0000200
|View full text |Cite
|
Sign up to set email alerts
|

Using reappraisal to regulate negative emotion after the 2016 U.S. Presidential election: Does emotion regulation trump political action?

Abstract: Political action (volunteering, protesting) is central to functioning democracies, and action is often motivated by negative emotion. However, theories of emotion regulation suggest that people often strive to decrease such negative emotions. Thus, effective emotion regulation (e.g., reappraisal)-while helping people feel better-could have the unintended consequence of hindering political action. We tested this hypothesis in Clinton voters after the 2016 U.S. election (N = 1552). Studies 1a (conducted November… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 67 publications
11
65
0
Order By: Relevance
“…For instance, in a context where a frustrating situation can be improved, it is sensible to try to change the situation rather than to use cognitive strategies to change how the situation is appraised. By contrast, in a context where nothing much could be done to improve the situation, it is sensible to use cognitive rather than situational strategies.…”
Section: Affect Regulationmentioning
confidence: 99%
“…For instance, in a context where a frustrating situation can be improved, it is sensible to try to change the situation rather than to use cognitive strategies to change how the situation is appraised. By contrast, in a context where nothing much could be done to improve the situation, it is sensible to use cognitive rather than situational strategies.…”
Section: Affect Regulationmentioning
confidence: 99%
“…On one hand, if experiencing positive emotions signals temporal satisfaction of a goal, such positive experiences could decrease the willingness to participate in subsequent actions. Moreover, recent research showed that lower negativity surrounding an issue obtained through reappraising the cause predicted weaker intentions to engage in political action (Ford, Feinberg, Lam, Mauss, & John, ). Thus, when positive experiences decrease negative affect associated with the cause they might reduce one's overall commitment to the cause.…”
Section: Activism As a Reaction To Negative Experiencesmentioning
confidence: 99%
“…In a cross‐sectional study of college students’ participation in the Black Lives Matter movement and in efforts to support the Deferred Action for Childhood Arrivals policy (Hope, Keels, & Durkee, ), factors including race/ethnicity, immigrant status, prior activism, and experiences of discrimination predicted differential involvement. And new research indicates that adults who voted for Hillary Clinton in the 2016 election and who regulated negative emotions effectively reported they were less likely to engage in political action after the election than adults who voted for Clinton who regulated negative emotions less effectively (Ford, Feinberg, Lam, Mauss, & John, ). Thus, young people with the same experiences may react differently to sociopolitical moments depending on race/ethnicity, personal experiences, or emotional reactivity.…”
Section: Historic Eventsmentioning
confidence: 99%